THE INFLUENCE OF PRODUCT PACKAGING, PROMOTION, AND PRICE TOWARD THE CUSTOMER SATISFACTION THAT LEADS TO THE GREEN ECONOMY ERA IN GARASI OUTLET IN SURABAYA - Kurniawati, Yuli; Kusmayati, Nindya Kartika; Wulansari, Dhyah (Accounting Study Program, Universitas Ciputra Surabaya, 2023)
ABSTRACT : In the modern era as we are today, there are a lot of small micro enterprises in culinary and food industry that compete in order to draw customer’s attention to buy. This research aims to understand and explains whether or not Product Packaging, Promotion, and Price influencing the Customer’s Satisfaction in the era of Green Economy. The method used here is the quantitative one categorized using descriptive approach with Surabaya people as population and sample is taken up randomly from the population. Sample used consists of 31 respondents. This research has normally distributed data, heteroscedasticity and multicollinearity-free, and none of auto-correlation symptoms found. The equation of this research has the form of multiple linear regression as follows; Y= 4,359 + 0,206X1 – 0,159X2 + 0,885X3. Result of the research shows that t test of Product Packaging (X1) and Promotion (X2) do not influence significantly toward the Customer Satisfaction (Y) partially, as it is found that sig value is larger than the alpha (0.05). Meanwhile, Price (X3) influences the Customer Satisfaction (Y) significantly. In F test, it is known that the value of sig is 0.00 which is less than the alpha (0.05) and the F score is 42.257 where this is definitely larger than the F table score which is 2.95 meaning that the three independent variables influence the dependent variable simultaneously. Keywords: Product Packaging, Promotion, Price, Green Economy